2016
DOI: 10.5455/ijmsph.2016.19112015270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urinary calcium-creatinine ratio as a diagnostic tool in the management of preeclampsia

Abstract: Background: Preeclampsia has a complex pathophysiology in which several studies have reported derangement in calcium metabolism. The decrease in urinary calcium and calcium-creatinine ratio (CCR) could be considered as a risk factor for development of preeclampsia. This ratio is easily measurable, most effective even with spot urine sample. Objective: To study the levels of urinary CCR and to correlate with proteinuria in preeclamptic patients and to assess the role of CCR in urine as a diagnostic marker in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Hypertension affects 5 to 10% of pregnant patients, making it the leading cause of maternal death in and around the world. Preeclampsia is diagnosed when a pregnant woman has high blood pressure (>140/90 mmHg) after the 20 th week of pregnancy (without a previous history of arterial hypertension) together with other symptoms [6,7]. These symptoms are now thought to be a late symptom of an illness that has been present since the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension affects 5 to 10% of pregnant patients, making it the leading cause of maternal death in and around the world. Preeclampsia is diagnosed when a pregnant woman has high blood pressure (>140/90 mmHg) after the 20 th week of pregnancy (without a previous history of arterial hypertension) together with other symptoms [6,7]. These symptoms are now thought to be a late symptom of an illness that has been present since the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium-to-creatinine ratio has been suggested by many to be a good screening test for preeclampsia [6] . Creatinine clearance is an indicator of the renal damage in pregnancy hypertension J Kar et al [7] noted that the ~ 159 ~ CCR had a Sensitivity of 75%, Specificity of 94.4%, PPV of 64.2%, NPV of 96.5%, Vahdat et al [8] noted that the Sensitivity of 77%, Specificity of 78% 54%, Dutt et al [9] , Sensitivity of 40% Specificity of 86.7%. Munge AM et al [10] noted that the CCR had a Sensitivity of 63.6, Specificity of 94.9% < PPV of 77.8 and NPV 90.2.…”
Section: Discussionmentioning
confidence: 99%
“…In another study undertaken by Izumi et al 12 during less than or equal to 12 weeks of gestation revealed measurement of calcium creatinine ratio to be of limited use in predicting preeclampsia, as 12weeks is too early for changes to appear. Dutt V et al 13 studied that pre-eclamptics admitted to the labor room for safe confinement have a significant hypocalciuria, however they found calcium creatinine ratio to have a low sensitivity and positive predictive value. Another study by Amandeep Kaur et al 14 found calcium creatinine ratio in the third trimester of pregnancy to be an effective predictor of the disease.…”
Section: Discussionmentioning
confidence: 99%